PROBLEMS FACED BY INDONESIAN EFL LEARNERS IN WRITING ARGUMENTATIVE ESSAY - Wulan Rahmatunisa (University of Kuningan, 2014)
Abstract:Â This study aims to find out problems in writing argumentative essay faced by Indonesian EFL learners. It is carried out in a qualitative research design as it attempted to describe the problems and their ways out. The data were taken from university studentsâ€™ writing task and interview. The participants are the second year of university Indonesia students who enrol their study in English Department. Results of the data indicated that Indonesian EFL learners faced the problems in three categories, those are linguistics problems, cognitive problems, and psychological problems. Mostly, students faced problems in linguistics related to the grammatical structure (23.2%), formatting words (30.2%), words classes (16.3%), error in using words (9.3%), and the use of article (21%). Second, cognitive problems are related to organizing paragraph, difficulties in remaining word classes, getting lost the generic structure, making a conclusion, and putting punctuation. Last, psychological problems which included laziness, egoism, bad mood, and difficulties to start writing also faced by Indonesian EFL learners. Data analysis also indicated the problem solving which hopefully will be beneficial for EFL teachers in writing class. It is strongly recommended that the EFL class should strengthen all the language skills in general and writing in particular, motivate the students to use English with the teachers, introduce pair work, peer-correction, and use dictionaries frequently etc.Keywords: argumentative essay, linguistics problems, cognitive problems, psychological problems